Flexible non-magnetic silicone rubber wave-absorbing patch and preparation method thereof

By using flexible magnetic-free silicone rubber and different types of carbon materials in the wave absorbing patch to build a hybrid network and construct a gradient impedance structure, the problems of short service life and high cost of existing magnetic wave absorbing patches under complex working conditions are solved, and efficient and stable electromagnetic wave absorption effect is achieved.

CN119562509APending Publication Date: 2025-03-04XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411837725.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing magnetic wave absorbing patches have high density and poor corrosion resistance, resulting in short service life in complex and extreme working conditions, low stability in wave absorbing effect and high cost.

Method used

Flexible magnetic-free silicone rubber is used as the substrate to build a hybrid network by filling different types of carbon materials to improve the absorbance performance, and a gradient impedance structure is built between the impedance matching layer and the absorbance layer to achieve broadband impedance matching.

Benefits of technology

It realizes continuous and wide-range regulation of electromagnetic parameters while reducing surface density, stable performance and low cost, and has potential wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562509A_ABST
    Figure CN119562509A_ABST
Patent Text Reader

Abstract

The invention provides a flexible non-magnetic silicone rubber wave-absorbing patch and a preparation method thereof, and belongs to the technical field of wave-absorbing materials. The wave-absorbing patch comprises a wave-absorbing layer and an impedance matching layer. The wave-absorbing layer is silicon rubber dispersed with first wave-absorbing filler, and the first wave-absorbing filler comprises at least two carbon materials; the impedance matching layer is silicone rubber dispersed with a second wave-absorbing filler, the second wave-absorbing filler comprises at least one carbon material, and the number of types of the carbon materials in the second wave-absorbing filler is less than or equal to the number of types of the carbon materials in the first wave-absorbing filler; wherein the total mass of the second wave-absorbing filler is smaller than that of the first wave-absorbing filler. The wave-absorbing patch can be combined with the corrosion resistance of silicone rubber, and is filled with different types of carbon materials to construct a hybrid network so as to improve the wave-absorbing performance, reduce the surface density, realize continuous wide-range regulation and control of electromagnetic parameters, construct a gradient impedance structure between layers, realize broadband impedance matching, and is stable in performance, relatively low in cost and suitable for industrial production. The method has a potential wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wave absorbing materials, and in particular relates to a flexible non-magnetic silicone rubber wave absorbing patch and a preparation method of the flexible non-magnetic silicone rubber wave absorbing patch. Background Art

[0002] Absorbing materials are usually used to solve electromagnetic radiation pollution and reduce the reflection of electromagnetic waves in the S, C, and X bands to reduce the impact on communication equipment. Absorbing materials can be used in the form of magnetic absorbing patches, and their absorbers are mainly made of magnetic materials such as carbonyl iron powder, iron silicon compounds, and ferrites.

[0003] However, the high density of magnetic materials makes the density of the composite material higher after filling, and the magnetic material has poor corrosion resistance. In complex and extreme working conditions, such as offshore wind turbine towers, the service life is short, the wave absorption effect is unstable and the cost is high.

[0004] The above information disclosed in the Background section is only for enhancement of understanding of the background of the present disclosure and therefore it may include information that does not constitute the prior art that is already known to one of ordinary skill in the art. Summary of the invention

[0005] The purpose of the embodiments of the present disclosure is to provide a flexible non-magnetic silicone rubber absorbing patch and a method for preparing the flexible non-magnetic silicone rubber absorbing patch, which can combine the corrosion resistance of the silicone rubber matrix, construct a hybrid network by filling different types of carbon materials to improve the absorbing performance, and achieve continuous and wide-range regulation of electromagnetic parameters while reducing the surface density, and construct a gradient impedance structure between the impedance matching layer and the absorbing layer to achieve broadband impedance matching, stable performance, low cost, and potential for broad application prospects.

[0006] In order to solve the above technical problems, the present disclosure is implemented as follows:

[0007] In a first aspect, the present disclosure provides a flexible non-magnetic silicone rubber absorbing patch, which may include an absorbing layer and an impedance matching layer; the absorbing layer is silicone rubber dispersed with a first absorbing filler, and the first absorbing filler includes at least two carbon materials; the impedance matching layer is silicone rubber dispersed with a second absorbing filler; the second absorbing filler includes at least one carbon material, and the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler; wherein the total mass of the second absorbing filler is less than the total mass of the first absorbing filler.

[0008] In an exemplary embodiment of the present disclosure, an intermediate layer is further included between the absorbing layer and the impedance matching layer; the intermediate layer is silicone rubber dispersed with a third absorbing filler; wherein the number of types of carbon materials in the third absorbing filler is less than or equal to the number of types of the first absorbing filler, and is greater than or equal to the number of types of the second absorbing filler; and the total mass of the third absorbing filler is less than the total mass of the first absorbing filler, and is greater than the total mass of the second absorbing filler.

[0009] In an exemplary embodiment of the present disclosure, the carbon material includes graphene, carbon nanotubes and carbon black.

[0010] In an exemplary embodiment of the present disclosure, the packing density of graphene is 0.05 to 0.1 g / cm 3 ; The bulk density of carbon nanotubes is 0.03 to 0.06 g / cm 3 ; The bulk density of carbon black is 0.02 to 0.05 g / cm 3 .

[0011] In an exemplary embodiment of the present disclosure, based on 100 parts of silicone rubber, the addition range of graphene in the first absorbing filler is 0 to 4 parts, the addition range of carbon nanotubes is 0 to 4 parts, and the addition range of carbon black is 20 to 40 parts.

[0012] In an exemplary embodiment of the present disclosure, based on 100 parts of silicone rubber, the addition range of graphene in the second absorbing filler is 0 to 1 part, the addition range of carbon nanotubes is 0 to 1 part, and the addition range of carbon black is 10 to 20 parts.

[0013] In an exemplary embodiment of the present disclosure, based on 100 parts of silicone rubber, the addition range of graphene in the third absorbing filler is 2 to 4 parts, the addition range of carbon nanotubes is 0 to 2 parts, and the addition range of carbon black is 20 to 25 parts.

[0014] In a second aspect, the present disclosure also provides a method for preparing a flexible non-magnetic silicone rubber absorbing patch, which may include: pulverizing at least two initial carbon materials to obtain corresponding at least two carbon materials, and determining a first absorbing filler and a second absorbing filler based on the carbon materials; wherein the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler, and the total mass of the second absorbing filler is less than the total mass of the first absorbing filler; the first absorbing filler includes at least two carbon materials; the second absorbing filler includes at least one carbon material; in the methyl vinyl silicone rubber, 2,5-dimethylsilicone rubber, During the mixing of methyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each carbon material in the first absorbing filler is added in batches, and then fumed silica is added, and the first mixed rubber is obtained after the mixing is completed; during the mixing of methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each carbon material in the second absorbing filler is added in batches, and then fumed silica is added, and the second mixed rubber is obtained after the mixing is completed; the first mixed rubber is used to prepare the absorbing layer, the second mixed rubber is used to prepare the impedance matching layer, and the flexible non-magnetic silicone rubber absorbing patch is obtained through a vulcanization process.

[0015] In an exemplary embodiment of the present disclosure, the first absorbing filler and the second absorbing filler are determined based on the carbon material, and further includes: determining a third absorbing filler based on the carbon material: wherein the number of types of carbon materials in the third absorbing filler is less than or equal to the number of types of the first absorbing filler, and greater than or equal to the number of types of the second absorbing filler; and the total mass of the third absorbing filler is less than the total mass of the first absorbing filler, and greater than the total mass of the second absorbing filler; after determining the first absorbing filler and the second absorbing filler based on the carbon material, further includes: in the methyl vinyl silicone rubber During the mixing process of rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each carbon material in the third absorbing filler is added in batches, and then fumed silica is added, and the third mixed rubber is obtained after the mixing is completed; the first mixed rubber is used to prepare the absorbing layer, the second mixed rubber is used to prepare the impedance matching layer, and the flexible non-magnetic silicone rubber absorbing patch is obtained through a vulcanization process, including: the first mixed rubber is used to prepare the absorbing layer, the second mixed rubber is used to prepare the impedance matching layer, and the third mixed rubber is used to prepare the intermediate layer, and the flexible non-magnetic silicone rubber absorbing patch is obtained through a vulcanization process.

[0016] In an exemplary embodiment of the present disclosure, a first rubber mix is ​​used to prepare an absorbing layer, a second rubber mix is ​​used to prepare an impedance matching layer, and a flexible non-magnetic silicone rubber absorbing patch is obtained through a vulcanization process, including: obtaining target performance parameters; performing structural design for the purpose of meeting the target performance parameters, obtaining a first thickness of the absorbing layer and a second thickness of the impedance matching layer; preparing an absorbing layer of a first thickness with the first rubber mix, preparing an impedance matching layer of a second thickness with the second rubber mix, and obtaining a flexible non-magnetic silicone rubber absorbing patch through a vulcanization process.

[0017] The disclosed embodiments provide a flexible non-magnetic silicone rubber absorbing patch and a method for preparing the flexible non-magnetic silicone rubber absorbing patch. The absorbing patch includes an absorbing layer and an impedance matching layer. The absorbing layer is silicone rubber dispersed with a first absorbing filler, and the first absorbing filler includes at least two carbon materials; the impedance matching layer is silicone rubber dispersed with a second absorbing filler, and the second absorbing filler includes at least one carbon material, and the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler; wherein the total mass of the second absorbing filler is less than the total mass of the first absorbing filler. The absorbing patch can combine the corrosion resistance of the silicone rubber matrix, construct a hybrid network by filling different types of carbon materials to improve the absorbing performance, realize continuous and wide-range regulation of electromagnetic parameters while reducing the surface density, and construct a gradient impedance structure between the impedance matching layer and the absorbing layer to achieve broadband impedance matching, stable performance, low cost, and potential for broad application prospects.

[0018] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0020] Figure 1 This is one of the structural schematic diagrams of the flexible non-magnetic silicone rubber absorbing patch provided in an embodiment of the present disclosure.

[0021] Figure 2 The second structural schematic diagram of the flexible non-magnetic silicone rubber absorbing patch provided in the embodiment of the present disclosure.

[0022] Figure 3 One of the step flow charts of the method for preparing the flexible non-magnetic silicone rubber absorbing patch provided in the embodiment of the present disclosure.

[0023] Figure 4 The second step flow chart of the method for preparing the flexible non-magnetic silicone rubber absorbing patch provided in the embodiment of the present disclosure.

[0024] Figure 5 A reflection loss curve diagram of the flexible non-magnetic silicone rubber absorbing patch prepared in Example 1 provided in an embodiment of the present invention.

[0025] Figure 6A reflection loss curve diagram of the flexible non-magnetic silicone rubber absorbing patch prepared in Example 4 provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present disclosure to clearly and completely describe the technical solutions in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0027] The terms "first", "second", etc. in the specification and claims of the present disclosure are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable when appropriate, so that the embodiments of the present disclosure can be implemented in an order other than those illustrated or described herein, and the objects distinguished by "first", "second", etc. are generally of the same type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the objects associated with each other are in an "or" relationship.

[0028] The terms "a", "an", "the" and "said" are used to indicate the presence of one or more elements / components / etc.; the terms "comprising" and "having" are used to indicate an open-ended inclusive meaning and mean that additional elements / components / etc. may be present in addition to the listed elements / components / etc.

[0029] Figure 1 This is one of the structural schematic diagrams of the flexible non-magnetic silicone rubber absorbing patch 100 provided in the embodiment of the present disclosure. Figure 1 As shown, the absorbing patch 100 may include an absorbing layer 110 and an impedance matching layer 120 .

[0030] The absorbing layer 110 is silicone rubber dispersed with a first absorbing filler, and the first absorbing filler includes at least two carbon materials; the impedance matching layer 120 is silicone rubber dispersed with a second absorbing filler; the second absorbing filler includes at least one carbon material, and the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler; wherein the total mass of the second absorbing filler is less than the total mass of the first absorbing filler.

[0031] In the disclosed embodiment, the absorbing patch 100 has a multilayer structure of an absorbing layer 110 and an impedance matching layer 120. The absorbing layer 110 and the impedance matching layer 120 are both based on silicone rubber, and the carbon material is dispersed in the silicone rubber system. The absorbing layer 110 is filled with a first absorbing filler, which includes at least two carbon materials. On this basis, it is also provided that the impedance matching layer 120 is filled with a second absorbing filler, which includes at least one carbon material, and the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler. Exemplarily, when the first absorbing filler includes two carbon materials, the second absorbing filler may include one or two carbon materials; when the first absorbing filler includes three carbon materials, the second absorbing filler may include one, two or three carbon materials, and so on when the number of types of carbon materials in the first absorbing filler increases.

[0032] On this basis, the total mass of the second absorbing filler can be less than the total mass of the first absorbing filler, so that the impedance from the impedance matching layer 120 to the absorbing layer 110 forms a gradient change from high to low.

[0033] Since the frequency response characteristics of a single type of carbon material are different, it is difficult to achieve broadband impedance matching. The disclosed embodiment uses a hybrid network composed of various carbon materials to effectively improve the absorbing performance, and the interlayer impedance gradient structure from the impedance matching layer 120 to the absorbing layer 110 can tune the frequency response characteristics of different carbon materials, so that the electromagnetic waves gradually enter the absorbing patch 100 and are lost between layers, reducing reflections, effectively improving the electromagnetic wave absorption rate, and widening the absorption band. Compared with electromagnetic materials, carbon materials can also reduce the surface density and achieve lightweight absorbing patch 100. At the same time, silicone rubber also has better corrosion resistance and flexibility, low processing cost, and can adapt to complex and extreme working environments, such as the ocean, thereby comprehensively improving the performance of the absorbing patch 100.

[0034] Figure 2 This is a second structural diagram of the flexible non-magnetic silicone rubber absorbing patch 200 provided in an embodiment of the present disclosure. Figure 2 As shown, the absorbing patch 200 may include an absorbing layer 210 and an impedance matching layer 220 , and may further include an intermediate layer 230 located between the absorbing layer 210 and the impedance matching layer 220 .

[0035] The absorbing layer 210 is silicone rubber dispersed with a first absorbing filler, and the first absorbing filler includes at least two carbon materials; the impedance matching layer 220 is silicone rubber dispersed with a second absorbing filler; the second absorbing filler includes at least one carbon material, and the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler; wherein the total mass of the second absorbing filler is less than the total mass of the first absorbing filler.

[0036] The middle layer 230 is silicone rubber dispersed with a third absorbing filler; wherein the number of types of carbon materials in the third absorbing filler is less than or equal to the number of types of the first absorbing filler, and greater than or equal to the number of types of the second absorbing filler; and the total mass of the third absorbing filler is less than the total mass of the first absorbing filler, and greater than the total mass of the second absorbing filler.

[0037] In the embodiment of the present disclosure, the absorbing layer 210 and the impedance matching layer 220 may correspond to the related descriptions of the absorbing layer 110 and the impedance matching layer 120 in the above-mentioned Figure 1, and will not be described again to avoid repetition.

[0038] In the embodiment of the present disclosure, an intermediate layer 230 may be further provided between the absorbing layer 210 and the impedance matching layer 220. The intermediate layer 230 also uses silicone rubber as a base, and disperses the carbon material in the silicone rubber system. The intermediate layer 230 uses a third absorbing filler, wherein the number of types of carbon materials in the third absorbing filler is equal to the number of types of macro carbon materials in the first absorbing filler. Exemplarily, when the first absorbing filler includes two carbon materials, the third absorbing filler may include two carbon materials; when the first absorbing filler includes three carbon materials, the third absorbing filler may include three carbon materials, and so on when the number of types of carbon materials in the first absorbing filler increases.

[0039] On this basis, the total mass of the third absorbing filler is less than the total mass of the first absorbing filler and greater than the total mass of the second absorbing filler, so that the impedance matching layer 220, the middle layer 230 and the absorbing layer 210 form a gradient impedance change from high to low.

[0040] In an optional embodiment of the present disclosure, the carbon material may include graphene, carbon nanotubes and carbon black.

[0041] In the embodiments of the present disclosure, the types of carbon materials may include two-dimensional graphene, one-dimensional carbon nanotubes, and zero-dimensional carbon black. When forming the absorbing layer, the impedance matching layer, and the intermediate layer, the types of carbon materials included in the first absorbing filler, the second absorbing filler, and the third absorbing filler may be independently selected from the aforementioned carbon materials. The types of the aforementioned carbon materials are only exemplary, and those skilled in the art may select other carbon materials based on actual cost conditions, application requirements, and other factors, and the embodiments of the present disclosure do not impose specific restrictions on this.

[0042] In an optional embodiment of the present disclosure, the packing density of graphene is 0.05 to 0.1 g / cm 3 .

[0043] In the embodiment of the present disclosure, the selected graphene packing density can be 0.05 g / cm 3 , or 0.1 g / cm 3 , or 0.05g / cm 3With 0.1g / cm 3 Any bulk density between, such as 0.055g / cm 3 , 0.06g / cm 3 , 0.07g / cm 3 etc.

[0044] In an optional embodiment of the present disclosure, the packing density of the carbon nanotubes is 0.03 to 0.06 g / cm 3 .

[0045] In the embodiment of the present disclosure, the selected carbon nanotube packing density can be 0.03 g / cm 3 , or 0.06g / cm 3 , or 0.03g / cm 3 With 0.06g / cm 3 Any bulk density between, such as 0.035g / cm 3 , 0.04g / cm 3 , 0.05g / cm 3 etc.

[0046] In an optional embodiment of the present disclosure, the bulk density of carbon black is 0.02 to 0.05 g / cm 3 .

[0047] In the embodiments of the present disclosure, the selected carbon black packing density can be 0.02 g / cm3, 0.05 g / cm3, or any packing density between 0.02 g / cm3 and 0.05 g / cm3, such as 0.035 g / cm3, 0.04 g / cm3, 0.05 g / cm3, etc.

[0048] It should be noted that the various carbon materials with the above-mentioned bulk density can be obtained directly, or the carbon materials with the initial bulk density can be obtained by crushing. 3 The graphene was crushed for 3 to 5 minutes to obtain a bulk density of 0.05 to 0.1 g / cm 3 Graphene; the initial packing density of the beads is 0.25 to 0.4 g / cm 3 The carbon nanotubes were crushed for 3 to 5 minutes to obtain a bulk density of 0.03 to 0.06 g / cm 3 Carbon nanotubes; the initial packing density of the beads is 0.5 to 0.8 g / cm 3 The carbon black was pulverized for 3 to 5 minutes to obtain a bulk density of 0.3 to 0.5 g / cm 3 The specific surface area of ​​the beaded graphene is 20 to 35 m 2 / g, the specific surface area of ​​carbon nanotubes is 150 to 200m 2 / g, carbon black specific surface area is 80 to 150m 2 / g.

[0049] In an optional embodiment of the present disclosure, based on 100 parts of silicone rubber, the addition range of graphene in the first absorbing filler is 0 to 4 parts, the addition range of carbon nanotubes is 0 to 4 parts, and the addition range of carbon black is 20 to 40 parts.

[0050] In the embodiment of the present disclosure, the first absorbing filler is dispersed in the silicone rubber. When determining the first absorbing filler among the three carbon materials of graphene, carbon nanotubes, and carbon black, it can be determined by the number of parts added per 100 parts by mass of the silicone rubber. Wherein, each part by mass can be 1g, 10g, etc., and the corresponding 100 parts by mass are 100g, 1000g, etc.

[0051] For example, the addition range of graphene is 0 to 4 parts. Specifically, 0 parts of graphene can be added to every 100 parts of silicone rubber, that is, no graphene is added; 4 parts of graphene can also be added, or any number between 0 and 4, such as 0.5, 1, 2, 3, etc. When each part is 1g, the addition range of graphene is 0 to 4g, when each part is 10g, the addition range of graphene is 0 to 40g, and so on when each part is increased.

[0052] The addition range of carbon nanotubes is 0 to 4 parts. Specifically, 0 parts of carbon nanotubes can be added to every 100 parts of silicone rubber, that is, no carbon nanotubes are added; 4 parts of carbon nanotubes can also be added, or any number between 0 and 4, such as 0.5, 1, 2, 3, etc. When each part is 1g, the addition range of carbon nanotubes is 0 to 4g, when each part is 10g, the addition range of carbon nanotubes is 0 to 40g, and so on when each part is increased.

[0053] The addition range of carbon black is 20 to 40 parts. Specifically, 20 parts of carbon black can be added to every 100 parts of silicone rubber; 40 parts of carbon black can also be added, or any number between 20 and 40, such as 25, 30, 35, etc. When each part is 1g, the addition range of carbon black is 20 to 40g, when each part is 10g, the addition range of carbon black is 200 to 400g, and so on when each part is increased.

[0054] It should be noted that the first absorbing filler includes at least two carbon materials. Therefore, among the three carbon materials of graphene, carbon nanotubes and carbon black, when the minimum addition of carbon black is 20 parts, at least one of the addition of graphene and carbon nanotubes is not 0 parts.

[0055] In an optional embodiment of the present disclosure, based on 100 parts of silicone rubber, the addition range of graphene in the second absorbing filler is 0 to 1 part, the addition range of carbon nanotubes is 0 to 1 part, and the addition range of carbon black is 10 to 20 parts.

[0056] In the embodiment of the present disclosure, the second absorbing filler is dispersed in the silicone rubber. When determining the second absorbing filler among the three carbon materials of graphene, carbon nanotubes, and carbon black, it can be determined by the number of parts added per 100 parts by mass of the silicone rubber. The mass of each part can be 1g, 10g, etc., and the corresponding 100 parts by mass are 100g, 1000g, etc.

[0057] For example, the addition range of graphene is 0 to 1 part. Specifically, 0 parts of graphene can be added to every 100 parts of silicone rubber, that is, no graphene is added; 1 part of graphene can also be added, or any number between 0 and 1, such as 0.1, 0.5, 0.6, etc. When each part is 1g, the addition range of graphene is 0 to 1g, when each part is 10g, the addition range of graphene is 0 to 10g, and so on when each part is increased.

[0058] The addition range of carbon nanotubes is 0 to 1 part. Specifically, 0 parts of carbon nanotubes can be added to every 100 parts of silicone rubber, that is, no carbon nanotubes are added; 1 part of carbon nanotubes can also be added, or any number between 0 and 1, such as 0.1, 0.5, 0.6, etc. When each part is 1g, the addition range of carbon nanotubes is 0 to 1g, when each part is 10g, the addition range of carbon nanotubes is 0 to 10g, and so on when each part is increased.

[0059] The addition range of carbon black is 10 to 20 parts. Specifically, 10 parts of carbon black can be added to every 100 parts of silicone rubber; 20 parts of carbon black can also be added, or any number between 10 and 20, such as 11, 15, 16, etc. When each part is 1g, the addition range of carbon black is 10 to 20g, when each part is 10g, the addition range of carbon black is 100 to 200g, and so on when each part is increased.

[0060] In an optional embodiment of the present disclosure, based on 100 parts of silicone rubber, the addition range of graphene in the third absorbing filler is 2 to 4 parts, the addition range of carbon nanotubes is 0 to 2 parts, and the addition range of carbon black is 20 to 25 parts.

[0061] In the embodiment of the present disclosure, the third absorbing filler is dispersed in the silicone rubber. When the third absorbing filler is determined among the three carbon materials of graphene, carbon nanotubes and carbon black, it can be determined by the number of parts added per 100 parts by mass of the silicone rubber. The mass of each part can be 1g, 10g, etc., and the corresponding 100 parts by mass are 100g, 1000g, etc.

[0062] For example, the addition range of graphene is 2 to 4 parts. Specifically, 2 parts of graphene can be added to every 100 parts of silicone rubber; 4 parts of graphene can also be added, or any number between 2 and 4, such as 2.5, 3, etc. When each part is 1g, the addition range of graphene is 2 to 4g, when each part is 10g, the addition range of graphene is 20 to 40g, and so on when each part is increased.

[0063] The addition range of carbon nanotubes is 0 to 2 parts. Specifically, 0 parts of carbon nanotubes can be added to every 100 parts of silicone rubber, that is, no carbon nanotubes are added; 2 parts of carbon nanotubes can also be added, or any number between 0 and 2, such as 0.5, 1, 1.5, etc. When each part is 1g, the addition range of carbon nanotubes is 0 to 2g, when each part is 10g, the addition range of carbon nanotubes is 0 to 20g, and so on when each part is increased.

[0064] The addition range of carbon black is 20 to 35 parts. Specifically, 10 parts of carbon black can be added to every 100 parts of silicone rubber; 20 parts of carbon black can also be added, or any number between 10 and 20, such as 11, 15, 16, etc. When each part is 1g, the addition range of carbon black is 10 to 20g, when each part is 10g, the addition range of carbon black is 100 to 200g, and so on when each part is increased.

[0065] Figure 3 This is a flow chart of the steps of the method for preparing the flexible non-magnetic silicone rubber absorbing patch provided in the embodiment of the present disclosure. Figure 3 As shown, the method may include the following steps 301 to 304:

[0066] Step 301: crush at least two initial carbon materials to obtain corresponding at least two carbon materials, and determine a first absorbing filler and a second absorbing filler based on the carbon materials; wherein the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler, and the total mass of the second absorbing filler is less than the total mass of the first absorbing filler; the first absorbing filler includes at least two carbon materials; and the second absorbing filler includes at least one carbon material.

[0067] In the embodiment of the present disclosure, the initial carbon material may be a carbon material with a relatively large stacking density and in the form of beads, which needs to be crushed before being applied to the preparation of subsequent absorbing patches. According to the requirements of the types of carbon materials in the subsequent feeding, the initial carbon material may include at least two types, wherein the rotation speed and time consumption of the crusher during the crushing process may be selected according to the initial stacking density and the required stacking density, such as crushing at a speed of 35,000 r / min for 3 to 5 minutes, and the embodiment of the present disclosure does not impose specific restrictions on this. On the basis of obtaining the carbon material by crushing the initial carbon material, the first absorbing filler and the second absorbing filler may be determined therefrom, that is, at least two types included in the first absorbing filler and at least one type included in the second absorbing filler are independently determined in the carbon material, the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler, and the total mass of the second absorbing filler is less than the total mass of the first absorbing filler. For details, please refer to the aforementioned Figure 1 To avoid repetition, the related descriptions of the first absorbing filler and the second absorbing filler are not repeated here.

[0068] Step 302: During the mixing of methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each carbon material in the first absorbing filler is added in batches, and then fumed silica is added, and after the mixing is completed, a first mixed rubber is obtained.

[0069] In the disclosed embodiment, the construction of the silicone rubber system can be realized based on raw materials such as methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane, hydroxy silicone oil and fumed silica. Methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane, hydroxy silicone oil and the like can be mixed and pre-mixed in a mixer. On the basis of pre-mixing, each carbon material in the first wave absorbing filler is added in batches, that is, one carbon material is added according to the type of carbon material, and then another carbon material is added after a period of time, until each carbon material is added to the mixing system, wherein the feeding interval time can be set according to the actual process conditions and preparation requirements, such as 10 to 15 minutes, and the disclosed embodiment does not impose specific restrictions on this. In the process of adding, the order of addition can be determined according to the difficulty of dispersion of different types of carbon materials and the size of the density, such as adding the more difficult to disperse first, adding the denser first, etc.; further, it can be added according to the dimension of the carbon material, such as adding the high-dimensional first, adding the low-dimensional later, etc. For example, among the three carbon materials of graphene, carbon nanotubes and carbon black, two-dimensional graphene can be added first to form a conductive network and enhance its mechanical strength, and then one-dimensional carbon nanotubes can be added to further improve the conductivity and mechanical strength, and finally zero-dimensional carbon black can be added to fill the gaps and optimize the overall performance of the hybrid network in the silicone rubber system. Determining the order of adding materials based on the structural characteristics of different carbon materials can improve the process stability and the stability of the electromagnetic absorption performance of silicone rubber.

[0070] In the embodiment of the present disclosure, when preparing the first rubber compound, 3 to 4 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane and 0.5 to 1 part of hydroxy silicone oil can be added to 100 parts of methyl vinyl silicone rubber for pre-mixing in an internal mixer. On this basis, 0 to 4 parts of graphene, 0 to 4 parts of carbon nanotubes and 20 to 40 parts of carbon black after crushing can be added in batches every 10 to 15 minutes for mixing; then 10 to 15 parts of fumed silica are added and mixed for 30 to 40 minutes, and the rubber compound is taken out and placed in an open mixer for 5 to 10 minutes to obtain the first rubber compound.

[0071] Step 303: During the mixing of methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each carbon material in the second absorbing filler is added in batches, and then fumed silica is added, and a second mixed rubber is obtained after the mixing is completed.

[0072] In the embodiment of the present disclosure, step 303 may correspond to the relevant description of the aforementioned step 302, and will not be described again here to avoid repetition.

[0073] In the embodiment of the present disclosure, when preparing the second rubber compound, 2 to 3 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane and 0.5 to 2 parts of hydroxy silicone oil can be added to 100 parts of methyl vinyl silicone rubber for pre-mixing in an internal mixer. On this basis, 0 to 1 part of graphene, 0 to 1 part of carbon nanotubes and 10 to 20 parts of carbon black after crushing can be added in batches every 10 to 20 minutes for mixing; then 30 to 40 parts of fumed silica are added and mixed for 30 to 40 minutes, and the rubber compound is taken out and placed in an open mixer for 5 to 10 minutes to obtain the first rubber compound.

[0074] Step 304: prepare an absorbing layer with the first rubber mixture and an impedance matching layer with the second rubber mixture, and obtain a flexible non-magnetic silicone rubber absorbing patch through a vulcanization process.

[0075] In the embodiment of the present disclosure, the first rubber compound can be used to prepare the absorbing layer, and the second rubber compound can be used to prepare the impedance matching layer, so as to obtain a flexible non-magnetic silicone rubber absorbing patch with the absorbing layer and the impedance matching layer superimposed. The superposition adopts a multi-layer superposition vulcanization process to mold the first rubber compound and the second rubber compound as a whole, and the vulcanization temperature can be 160 to 180°C, the vulcanization pressure can be selected to be 5MPa, and the vulcanization time can be 7 to 10min.

[0076] In an optional embodiment of the present disclosure, step 304 may include the following steps A1 to A3.

[0077] Step A1: Obtain target performance parameters.

[0078] In the embodiment of the present disclosure, the target performance parameter may be a performance parameter of the flexible non-magnetic silicone rubber absorbing patch, such as the working bandwidth; the thickness, density and other parameters of the flexible non-magnetic silicone rubber absorbing patch may also be further limited. The target performance parameter may be obtained by analyzing the actual working environment of the flexible non-magnetic silicone rubber absorbing patch, or may be provided by the demander, and the embodiment of the present disclosure does not impose any specific restrictions on this.

[0079] Step A2: Design the structure to meet the target performance parameters, and obtain a first thickness of the absorbing layer and a second thickness of the impedance matching layer.

[0080] In the disclosed embodiment, simulation calculations may be performed for the purpose of meeting target performance parameters to determine the first thickness of the absorbing layer and the second thickness of the impedance matching layer in this case, thereby achieving the overall structural design of the flexible non-magnetic silicone rubber absorbing patch.

[0081] Step A3: using the first rubber mix to prepare an absorbing layer of a first thickness, using the second rubber mix to prepare an impedance matching layer of a second thickness, and obtaining a flexible non-magnetic silicone rubber absorbing patch through a vulcanization process.

[0082] In the embodiment of the present disclosure, based on the determination of the first thickness and the second thickness, the first rubber mix can be used to prepare the first thickness of the absorbing layer, and the second rubber mix can be used to prepare the second thickness of the impedance matching layer, and the vulcanization process can be used to prepare the flexible non-magnetic silicone rubber absorbing patch. For details, please refer to the relevant description of the aforementioned step 304, which will not be repeated here to avoid repetition.

[0083] Figure 4 The second step flow chart of the method for preparing the flexible non-magnetic silicone rubber absorbing patch provided in the embodiment of the present disclosure. Figure 4 As shown, the method may include the following steps 401 to 406:

[0084] Step 401: crush at least two initial carbon materials to obtain corresponding at least two carbon materials, and determine a first absorbing filler and a second absorbing filler based on the carbon materials; wherein the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler, and the total mass of the second absorbing filler is less than the total mass of the first absorbing filler; the first absorbing filler includes at least two carbon materials; and the second absorbing filler includes at least one carbon material.

[0085] In the embodiment of the present disclosure, the first absorbing filler and the second absorbing filler may correspond to the relevant description of the aforementioned step 301, and will not be described again here to avoid repetition.

[0086] Step 402: Determine a third absorbing filler based on carbon materials: wherein the number of types of carbon materials in the third absorbing filler is less than or equal to the number of types of the first absorbing filler, and is greater than or equal to the number of types of the second absorbing filler; and the total mass of the third absorbing filler is less than the total mass of the first absorbing filler, and is greater than the total mass of the second absorbing filler.

[0087] In the embodiment of the present disclosure, on the basis of obtaining the carbon material by pulverizing the initial carbon material, the third filler can be determined therefrom, that is, at least two types of the third absorbing filler are independently determined in the carbon material, the number of types of carbon materials in the third absorbing filler is less than or equal to the number of types of the first absorbing filler, and greater than or equal to the number of types of the second absorbing filler; and the total mass of the third absorbing filler is less than the total mass of the first absorbing filler, and greater than the total mass of the second absorbing filler. For details, please refer to the aforementioned Figure 1 To avoid repetition, the relevant description of the third absorbing filler will not be repeated here.

[0088] Step 403, during the mixing process of methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each carbon material in the first absorbing filler is added in batches, and then fumed silica is added, and after the mixing is completed, a first mixed rubber is obtained.

[0089] In the embodiment of the present disclosure, step 403 may correspond to the relevant description of the aforementioned step 302, and will not be described again here to avoid repetition.

[0090] Step 404: during the mixing of methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each carbon material in the second absorbing filler is added in batches, and then fumed silica is added, and after the mixing is completed, a second mixed rubber is obtained.

[0091] In the embodiment of the present disclosure, step 404 may correspond to the relevant description of the aforementioned step 303, and will not be described again here to avoid repetition.

[0092] Step 405: During the mixing of methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each carbon material in the third absorbing filler is added in batches, and then fumed silica is added, and after the mixing is completed, a third mixed rubber is obtained.

[0093] In the embodiment of the present disclosure, step 405 may correspond to the relevant description of the aforementioned step 302 and step 303, and will not be described again here to avoid repetition.

[0094] In the embodiment of the present disclosure, when preparing the third rubber compound, 3 to 4 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane and 1 part of hydroxy silicone oil can be added to 100 parts of methyl vinyl silicone rubber for pre-mixing in an internal mixer. On this basis, 2 to 4 parts of graphene, 0 to 2 parts of carbon nanotubes and 20 to 25 parts of carbon black after crushing can be added in batches every 10 to 15 minutes for mixing; then 25 to 30 parts of fumed silica are added and mixed for 30 to 40 minutes, and the rubber compound is taken out and placed in an open mixer for 5 to 10 minutes to obtain the first rubber compound.

[0095] Step 406: prepare an absorbing layer with the first rubber mix, prepare an impedance matching layer with the second rubber mix, and prepare an intermediate layer with the third rubber mix, and obtain a flexible non-magnetic silicone rubber absorbing patch through a vulcanization process.

[0096] In the embodiment of the present disclosure, step 406 may correspond to the relevant description of the aforementioned step 304, and will not be described again here to avoid repetition.

[0097] It should be noted that the above-mentioned mass, time, temperature, pressure, rotation speed and other parameter values ​​are all exemplary descriptions. Those skilled in the art can select specific values ​​according to actual process conditions, raw material characteristics and performance requirements, and the embodiments of the present disclosure do not impose specific limitations on this.

[0098] Exemplarily, the disclosed embodiment also provides a preparation example of a flexible non-magnetic silicone rubber absorbing patch as shown below:

[0099] Example 1

[0100] The flexible non-magnetic silicone rubber absorbing patch of this embodiment includes an absorbing layer and an impedance matching layer, and the preparation steps are as follows:

[0101] Step 1: Crushing of carbon materials.

[0102] Weigh 3 parts of graphene, 3 parts of carbon nanotubes, and 30 parts of carbon black, place them in a grinder, grind them at a speed of 35000 r / min for 5 minutes, and set aside.

[0103] Step 2: Prepare a first rubber mix and a second rubber mix.

[0104] First mix:

[0105] Step 211, add 100 parts of methyl vinyl silicone rubber, 4 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 0.5 parts of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0106] Step 212: every 15 minutes, 3 parts of graphene, 2 parts of carbon nanotubes and 20 parts of carbon black after the pulverization treatment are added in batches in sequence for mixing at a rotation speed of 40 r / min.

[0107] Step 213, add 30 parts of fumed silica and mix for 40 minutes.

[0108] Step 214, taking the rubber mix and placing it on an open mixer for 5 minutes, and then leaving it to stand for 24 hours to obtain a first rubber mix.

[0109] Second mix:

[0110] Step 221, add 100 parts of methyl vinyl silicone rubber, 2 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 1 part of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0111] Step 222: Every 10 minutes, add 1 part of the crushed carbon nanotubes and 10 parts of carbon black in batches for mixing at a rotation speed of 40 r / min.

[0112] Step 223, add 40 parts of fumed silica and mix for 30 minutes.

[0113] Step 224, taking the rubber mix and placing it on an open mixer for 10 minutes, and then leaving it to stand for 24 hours to obtain a second rubber mix.

[0114] Step 3: Prepare a flexible non-magnetic silicone rubber absorbing patch.

[0115] The structure is designed according to the target performance parameter of reflectivity RL≤10dB in the X-band, and the corresponding thicknesses of the absorbing layer and the impedance matching layer are obtained. The first rubber compound and the second rubber compound are integrally molded and vulcanized through a multi-layer superposition vulcanization process to obtain a flexible non-magnetic silicone rubber absorbing patch, wherein the vulcanization temperature is 170°C, the vulcanization pressure is 5MPa, and the vulcanization time is 7min.

[0116] Example 2

[0117] The flexible non-magnetic silicone rubber absorbing patch of this embodiment includes an absorbing layer and an impedance matching layer, and the preparation steps are as follows:

[0118] Step 1: Crushing of carbon materials.

[0119] Weigh 5 parts of graphene and 45 parts of carbon black and place them in a pulverizer respectively, and pulverize them at a speed of 35000 r / min for 4 minutes before use.

[0120] Step 2: Prepare a first rubber mix and a second rubber mix.

[0121] First mix:

[0122] Step 211, add 100 parts of methyl vinyl silicone rubber, 3 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 1 part of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0123] Step 212: Every 15 minutes, 4 parts of the pulverized graphene and 25 parts of carbon black are added in batches for mixing at a rotation speed of 40 r / min.

[0124] Step 213, add 25 parts of fumed silica and mix for 30 minutes.

[0125] Step 214, taking the rubber mix, placing it on an open mixer for 10 minutes, and then leaving it to stand for 24 hours to obtain a first rubber mix.

[0126] Second mix:

[0127] Step 221, add 100 parts of methyl vinyl silicone rubber, 2 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 0.5 parts of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0128] Step 222: Every 15 minutes, add 1 part of the pulverized graphene and 20 parts of carbon black in batches for mixing at a rotation speed of 40 r / min.

[0129] Step 223, add 30 parts of fumed silica and mix for 40 minutes.

[0130] Step 224, taking the rubber mix and placing it on an open mixer for 10 minutes, and then leaving it to stand for 24 hours to obtain a second rubber mix.

[0131] Step 3: Prepare a flexible non-magnetic silicone rubber absorbing patch.

[0132] The structure is designed according to the target performance parameter of reflectivity RL≤10dB in the X-band, and the corresponding thicknesses of the absorbing layer and the impedance matching layer are obtained. The first rubber compound and the second rubber compound are integrally molded and vulcanized through a multi-layer superposition vulcanization process to obtain a flexible non-magnetic silicone rubber absorbing patch, wherein the vulcanization temperature is 180°C, the vulcanization pressure is 5MPa, and the vulcanization time is 8min.

[0133] Example 3

[0134] The flexible non-magnetic silicone rubber absorbing patch of this embodiment includes an absorbing layer and an impedance matching layer, and the preparation steps are as follows:

[0135] Step 1: Crushing of carbon materials.

[0136] Weigh 4 parts of carbon nanotubes and 40 parts of carbon black, place them in a grinder, grind them at a speed of 35000 r / min for 3 minutes and set aside.

[0137] Step 2: Prepare a first rubber mix and a second rubber mix.

[0138] First mix:

[0139] Step 211, add 100 parts of methyl vinyl silicone rubber, 3 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 0.5 parts of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0140] Step 212: Every 15 minutes, 4 parts of the crushed carbon nanotubes and 30 parts of carbon black are added in batches for mixing at a rotation speed of 40 r / min.

[0141] Step 213, add 20 parts of fumed silica and mix for 35 minutes.

[0142] Step 214, taking the rubber mix, placing it on an open mixer for 10 minutes, and then leaving it to stand for 24 hours to obtain a first rubber mix.

[0143] Second mix:

[0144] Step 221, add 100 parts of methyl vinyl silicone rubber, 3 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 2 parts of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0145] Step 222, add 10 parts of crushed carbon black and mix them at a rotation speed of 40r / min and mix for 20 minutes.

[0146] Step 223, add 40 parts of fumed silica and mix for 40 minutes.

[0147] Step 224, taking the rubber mix and placing it on an open mixer for 5 minutes, and then leaving it to stand for 24 hours to obtain a second rubber mix.

[0148] Step 3: Prepare a flexible non-magnetic silicone rubber absorbing patch.

[0149] The structure is designed according to the target performance parameter of reflectivity RL≤10dB in the X-band, and the corresponding thicknesses of the absorbing layer and the impedance matching layer are obtained. The first rubber compound and the second rubber compound are integrally molded and vulcanized through a multi-layer superposition vulcanization process to obtain a flexible non-magnetic silicone rubber absorbing patch, wherein the vulcanization temperature is 170°C, the vulcanization pressure is 5MPa, and the vulcanization time is 8min.

[0150] Example 4

[0151] The flexible non-magnetic silicone rubber absorbing patch of this embodiment includes an absorbing layer, an intermediate layer and an impedance matching layer. The preparation steps are as follows:

[0152] Step 1: Crushing of carbon materials.

[0153] Weigh 7 parts of graphene, 5 parts of carbon nanotubes, and 55 parts of carbon black, respectively, place them in a pulverizer, pulverize them at a rotation speed of 35000 r / min for 5 minutes, and then set aside.

[0154] Step 2: Prepare a first rubber mix, a second rubber mix and a third rubber mix respectively.

[0155] First mix:

[0156] Step 211, add 100 parts of methyl vinyl silicone rubber, 3 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 1 part of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0157] Step 212: Every 10 minutes, 4 parts of graphene, 3 parts of carbon nanotubes and 25 parts of carbon black after the pulverization process are added in batches in sequence for mixing at a rotation speed of 40 r / min.

[0158] Step 213, add 25 parts of fumed silica and mix for 30 minutes.

[0159] Step 214, taking the rubber mix and placing it on an open mixer for 5 minutes, and then leaving it to stand for 24 hours to obtain a second rubber mix.

[0160] Second mix:

[0161] Step 221, add 100 parts of methyl vinyl silicone rubber, 2 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 2 parts of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0162] Step 222: Every 15 minutes, add 1 part of the pulverized graphene and 10 parts of carbon black in batches for mixing at a rotation speed of 40 r / min.

[0163] Step 223, add 40 parts of fumed silica and mix for 35 minutes.

[0164] Step 224, taking the rubber mix and placing it on an open mixer for 10 minutes, and then leaving it to stand for 24 hours to obtain a second rubber mix.

[0165] Third mix:

[0166] Step 231, add 100 parts of methyl vinyl silicone rubber, 4 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 1 part of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0167] Step 232: 2 parts of graphene, 2 parts of carbon nanotubes and 20 parts of carbon black after the pulverization process are added in batches in sequence and mixed at a rotation speed of 40 r / min.

[0168] Step 233, add 30 parts of fumed silica and mix for 40 minutes.

[0169] Step 234, taking the rubber mix, placing it on an open mixer for 5 minutes, and then leaving it to stand for 24 hours to obtain a third rubber mix.

[0170] Step 3: Flexible non-magnetic silicone rubber absorbing patch.

[0171] The structure is designed according to the target performance parameter of reflectivity RL≤10dB in the X-band, and the corresponding thicknesses of the absorbing layer, the impedance matching layer and the intermediate layer are obtained. The first rubber compound, the second rubber compound and the third rubber compound are integrally molded and vulcanized through a multi-layer superposition vulcanization process to obtain a flexible non-magnetic silicone rubber absorbing patch, wherein the vulcanization temperature is 170°C, the vulcanization pressure is 5MPa, and the vulcanization time is 8min.

[0172] Example 5

[0173] The flexible non-magnetic silicone rubber absorbing patch of this embodiment includes an absorbing layer, an intermediate layer and an impedance matching layer. The preparation steps are as follows:

[0174] Step 1: Crushing of carbon materials.

[0175] Weigh 5 parts of graphene, 5 parts of carbon nanotubes, and 75 parts of carbon black, respectively, and place them in a pulverizer, and pulverize them at a rotation speed of 35000 r / min for 4 minutes before use.

[0176] Step 2: Prepare a first rubber mix, a second rubber mix and a third rubber mix respectively.

[0177] First mix:

[0178] Step 211, add 100 parts of methyl vinyl silicone rubber, 4 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 0.5 parts of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0179] Step 212: Every 15 minutes, add 1 part of the pulverized graphene, 4 parts of carbon nanotubes and 40 parts of carbon black in batches for mixing at a rotation speed of 40 r / min.

[0180] Step 213, add 10 parts of fumed silica and mix for 40 minutes.

[0181] Step 214, taking the rubber mix, placing it on an open mixer for 10 minutes, and then leaving it to stand for 24 hours to obtain a first rubber mix.

[0182] Second mix:

[0183] Step 221, add 100 parts of methyl vinyl silicone rubber, 2 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 2 parts of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0184] Step 222: Every 10 minutes, add 1 part of the crushed carbon nanotubes and 15 parts of carbon black in batches for mixing at a rotation speed of 40 r / min.

[0185] Step 223, add 35 parts of fumed silica and mix for 35 minutes.

[0186] Step 224, taking the rubber mix and placing it on an open mixer for 10 minutes, and then leaving it to stand for 24 hours to obtain a second rubber mix.

[0187] Third mix:

[0188] Step 231, add 100 parts of methyl vinyl silicone rubber, 3 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 1 part of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0189] Step 232: Every 15 minutes, 4 parts of graphene and 20 parts of carbon black after the crushing treatment are added in batches for mixing at a rotation speed of 40 r / min.

[0190] Step 233, add 30 parts of fumed silica and mix for 30 minutes.

[0191] Step 234, taking the rubber mix, placing it on an open mixer for 5 minutes, and then leaving it to stand for 24 hours to obtain a third rubber mix.

[0192] Step 3: Prepare a flexible non-magnetic silicone rubber absorbing patch.

[0193] The structure is designed according to the target performance parameter of reflectivity RL≤10dB in the X-band, and the corresponding thicknesses of the absorbing layer, the impedance matching layer and the intermediate layer are obtained. The first rubber compound, the second rubber compound and the third rubber compound are integrally molded and vulcanized through a multi-layer superposition vulcanization process to obtain a flexible non-magnetic silicone rubber absorbing patch, wherein the vulcanization temperature is 180°C, the vulcanization pressure is 5MPa, and the vulcanization time is 6min.

[0194] Example 6

[0195] The flexible non-magnetic silicone rubber absorbing patch of this embodiment includes an absorbing layer, an intermediate layer and an impedance matching layer. The preparation steps are as follows:

[0196] Step 1: Crushing of carbon materials.

[0197] Weigh 5 parts of graphene, 4 parts of carbon nanotubes, and 65 parts of carbon black, respectively, and place them in a pulverizer, pulverize them at a speed of 35000 r / min for 3 minutes, and then set aside.

[0198] Step 2: Prepare a first rubber mix, a second rubber mix and a third rubber mix respectively.

[0199] First mix:

[0200] Step 211, add 100 parts of methyl vinyl silicone rubber, 3 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 1 part of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0201] Step 212: Every 10 minutes, 2 parts of graphene, 3 parts of carbon nanotubes and 30 parts of carbon black after the pulverization process are added in batches in sequence for mixing at a rotation speed of 40 r / min.

[0202] Step 213, add 20 parts of fumed silica and mix for 40 minutes.

[0203] Step 214, taking the rubber mix, placing it on an open mixer for 10 minutes, and then leaving it to stand for 24 hours to obtain a first rubber mix.

[0204] Second mix:

[0205] Step 221, add 100 parts of methyl vinyl silicone rubber, 3 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 2 parts of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0206] Step 222, add 10 parts of crushed carbon black and mix them at a rotation speed of 40 r / min and a mixing time of 10 min.

[0207] Step 223, add 40 parts of fumed silica and mix for 30 minutes.

[0208] Step 224, taking the rubber mix and placing it on an open mixer for 5 minutes, and then leaving it to stand for 24 hours to obtain a second rubber mix.

[0209] Third mix:

[0210] Step 231, add 100 parts of methyl vinyl silicone rubber, 4 parts of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and 1 part of hydroxy silicone oil into an internal mixer and pre-mix for 5 minutes.

[0211] Step 232: Every 15 minutes, 3 parts of graphene, 1 part of carbon nanotubes and 25 parts of carbon black after the pulverization process are added in batches in sequence for mixing at a rotation speed of 40 r / min.

[0212] Step 233, add 25 parts of fumed silica and mix for 30 minutes.

[0213] Step 234, taking the rubber mix, placing it on an open mixer for 5 minutes, and then leaving it to stand for 24 hours to obtain a third rubber mix.

[0214] Step 3: Prepare a multi-layered flexible non-magnetic silicone rubber absorbing patch.

[0215] The structure is designed according to the target performance parameter of reflectivity RL≤10dB in the X-band, and the corresponding thicknesses of the absorbing layer, the impedance matching layer and the intermediate layer are obtained. The first rubber compound, the second rubber compound and the third rubber compound are integrally molded and vulcanized through a multi-layer superposition vulcanization process to obtain a flexible non-magnetic silicone rubber absorbing patch, wherein the vulcanization temperature is 160°C, the vulcanization pressure is 5MPa, and the vulcanization time is 5min.

[0216] Based on the flexible non-magnetic silicone rubber absorbing patch prepared in the above-mentioned Examples 1 to 6, the electromagnetic parameters of the absorbing patch sample in the frequency range of 2 to 18 GHz were tested by coaxial electromagnetic parameter test; the mechanical properties were tested in accordance with GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", and the tensile strength and elongation at break of the sample were tested, wherein the tensile speed was set to 500 mm / min. As shown below, Table 1 shows the test results of absorbing performance, mechanical properties and anti-corrosion performance:

[0217] Table 1

[0218]

[0219]

[0220] As shown in Table 1, the density of the flexible non-magnetic silicone rubber absorbing patch constructed by Examples 1 to 6 is relatively low, ranging from 1 to 1.4 g / cm3 , is much smaller than the existing magnetic rubber absorbing materials; from the absorbing performance point of view, Figure 5 A reflection loss curve of the flexible non-magnetic silicone rubber absorbing patch prepared in Example 1 is provided, wherein the ordinate is the reflection loss (Reflection loss), and the abscissa is the absorbing frequency (Frequency). The absorbing patch prepared in Example 1 has a thickness of 2 mm, reaches a maximum absorption intensity of -18.82 dB at 10.70 GHz, and the absorption intensity is below -10 dB in the range of 8.57 to 12.37 GHz, with an effective bandwidth of 3.8 GHz; similarly, Figure 6 The reflection loss curve of the flexible non-magnetic silicone rubber absorbing patch prepared in Example 4 is provided. When the thickness of the absorbing patch prepared in Example 4 is 3 mm, it shows more outstanding absorbing performance, reaching a maximum absorption intensity of -47.68 dB at 9.66 GHz, and an effective bandwidth of 4.12 GHz below -10 dB, which can completely cover the X-band electromagnetic wave loss and has excellent absorbing performance. The flexible non-magnetic silicone rubber absorbing patch prepared in the above embodiment also combines the characteristics of easy processing of silicone rubber, mechanical properties, corrosion resistance and weather resistance, and can meet the absorbing application requirements under complex and extreme working conditions.

[0221] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

Claims

1. A flexible non-magnetic silicone rubber absorbing patch, characterized in that: The absorbing patch comprises an absorbing layer and an impedance matching layer; The wave absorbing layer is silicone rubber dispersed with a first wave absorbing filler, and the first wave absorbing filler includes at least two carbon materials; The impedance matching layer is silicone rubber dispersed with a second absorbing filler; the second absorbing filler includes at least one carbon material, and the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler; Wherein, the total mass of the second absorbing filler is less than the total mass of the first absorbing filler.

2. The absorbing patch according to claim 1, characterized in that: It also includes an intermediate layer located between the absorbing layer and the impedance matching layer; The middle layer is silicone rubber dispersed with a third wave absorbing filler; The number of types of carbon materials in the third absorbing filler is less than or equal to the number of types of the first absorbing filler, and is greater than or equal to the number of types of the second absorbing filler; and the total mass of the third absorbing filler is less than the total mass of the first absorbing filler, and is greater than the total mass of the second absorbing filler.

3. The absorbing patch according to claim 2, characterized in that: The carbon materials include graphene, carbon nanotubes and carbon black.

4. The absorbing patch according to claim 3, characterized in that: The packing density of the graphene is 0.05 to 0.1 g / cm 3 ; The packing density of the carbon nanotubes is 0.03 to 0.06 g / cm 3 ; The bulk density of the carbon black is 0.02 to 0.05 g / cm 3 .

5. The absorbing patch according to claim 3, characterized in that: Based on 100 parts of silicone rubber, the addition range of the graphene in the first wave-absorbing filler is 0 to 4 parts, the addition range of the carbon nanotube is 0 to 4 parts, and the addition range of the carbon black is 20 to 40 parts.

6. The absorbing patch according to claim 3, characterized in that: Based on 100 parts of silicone rubber, the addition range of the graphene in the second wave-absorbing filler is 0 to 1 part, the addition range of the carbon nanotube is 0 to 1 part, and the addition range of the carbon black is 10 to 20 parts.

7. The absorbing patch according to claim 3, characterized in that: Based on 100 parts of silicone rubber, the addition range of the graphene in the third absorbing filler is 2 to 4 parts, the addition range of the carbon nanotube is 0 to 2 parts, and the addition range of the carbon black is 20 to 25 parts.

8. A method for preparing a flexible non-magnetic silicone rubber absorbing patch, characterized in that: The method comprises: at least two initial carbon materials are crushed to obtain corresponding at least two carbon materials, and a first absorbing filler and a second absorbing filler are determined based on the carbon materials; wherein the number of types of carbon materials in the second absorbing filler is less than or equal to the number of types of carbon materials in the first absorbing filler, and the total mass of the second absorbing filler is less than the total mass of the first absorbing filler; the first absorbing filler includes at least two carbon materials; and the second absorbing filler includes at least one carbon material; During the mixing process of methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each of the carbon materials in the first absorbing filler is added in batches, and then fumed silica is added, and a first mixed rubber is obtained after the mixing is completed; During the mixing process of methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each of the carbon materials in the second wave absorbing filler is added in batches, and then fumed silica is added, and a second mixed rubber is obtained after the mixing is completed; The first rubber mixture is used to prepare an absorbing layer, the second rubber mixture is used to prepare an impedance matching layer, and the flexible non-magnetic silicone rubber absorbing patch is obtained through a vulcanization process.

9. The method according to claim 8, characterized in that The determining of the first absorbing filler and the second absorbing filler based on the carbon material further includes: Determining a third absorbing filler based on the carbon material: wherein the number of types of carbon materials in the third absorbing filler is less than or equal to the number of types of the first absorbing filler, and greater than or equal to the number of types of the second absorbing filler; and the total mass of the third absorbing filler is less than the total mass of the first absorbing filler, and greater than the total mass of the second absorbing filler; After determining the first absorbing filler and the second absorbing filler based on the carbon material, the method further includes: During the mixing of methyl vinyl silicone rubber, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane and hydroxy silicone oil, each of the carbon materials in the third absorbing filler is added in batches, and then fumed silica is added, and a third mixed rubber is obtained after the mixing is completed; The method of preparing the absorbing layer with the first rubber mix and the impedance matching layer with the second rubber mix, and obtaining the flexible non-magnetic silicone rubber absorbing patch through a vulcanization process comprises: The first rubber mix is ​​used to prepare an absorbing layer, the second rubber mix is ​​used to prepare an impedance matching layer, and the third rubber mix is ​​used to prepare an intermediate layer, and the flexible non-magnetic silicone rubber absorbing patch is obtained through a vulcanization process.

10. The method according to claim 8, characterized in that The method of preparing the absorbing layer with the first rubber mix and the impedance matching layer with the second rubber mix, and obtaining the flexible non-magnetic silicone rubber absorbing patch through a vulcanization process comprises: Obtain target performance parameters; Performing structural design for the purpose of meeting the target performance parameters, and obtaining a first thickness of the absorbing layer and a second thickness of the impedance matching layer; The first rubber compound is used to prepare the absorbing layer of the first thickness, and the second rubber compound is used to prepare the impedance matching layer of the second thickness, and the flexible non-magnetic silicone rubber absorbing patch is obtained through a vulcanization process.